Character Education For Peace: An Effective Strategy To Reduce Violence In Schools - Agusman, Desi Destiana; Giwangsa, Sendi Fauzi; Hergiana, Syadni Nur Cikal; Sulistiowaty, Gadis (International Conference on Elementary Education, 2025)
This study aims to identify and analyze the peaceful character profile of elementary school students in Cimanggung District, Sumedang Regency. Peaceful character is a crucial aspect in building a conducive educational environment, especially in reducing violent behavior in students. This research uses a qualitative method, with data collection techniques including interviews, observations, and document analysis. The results of the study show that the peaceful character of students in the region still needs to be strengthened, especially in the aspects of empathy, tolerance, and peaceful conflict resolution. Factors such as family environment, school, and peer influence play an important role in developing students' character to be better in accordance with the expectations they want to achieve. Therefore, this study recommends more structured educational interventions including teacher training and character education programs that focus on promoting peaceful attitudes. This finding is expected to be a reference for educational institutions in creating a safe and harmonious learning atmosphere in elementary schools